SISTEM INFORMASI AKADEMIK SMP NEGERI 2 TALANG EMPAT BERBASIS WEB - Eko Putra Membara; Liza Yulianti; Indra Kanedi (Jurnal Media Infotama, 2014)
The objective of this research is to make academic information system of SMP Negeri 2 Talang Empat. The system is web-based, which designed and realized using the programming language PHP and MySQL database. The menu in Aca-demic Information Systems of SMP Negeri 2 Talang Empat is divided into several main menus, namely home menu, menu information, menu material, news menu, menu galleries, guest books and menu navigation admin. For information consists of a sub-class data menu, sub menu Master data information, data information Student sub menu, sub menu infromasi Data Value, sub menu data information Alumni and sub menu data information Lessons. With the website SMP Negeri 2 Talang Empat, the school already has an alternative media provider of information, making it easier to search data on Junior High School 2 Talang Empat.Keyword: website, school, academic information system.